2018
DOI: 10.1021/acscatal.8b00905
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hydrogen Evolution Reaction in Electrochemical N2 Reduction Using Single-Atom Catalysts: A Computational Guideline

Abstract: We studied electrochemical nitrogen reduction reactions (NRR) to ammonia on single atom catalysts (SACs) anchored on defective graphene derivatives by density functional calculations. We find significantly improved NRR selectivity on SACs compared to that on the existing bulk metal surface due to the great suppression of the hydrogen evolution reaction (HER) on SACs with the help of the ensemble effect. In addition, several SACs, including Ti@N4 (0.69 eV) and V@N4 (0.87 eV), are shown to exhibit lower free ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
558
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(581 citation statements)
references
References 50 publications
20
558
2
1
Order By: Relevance
“…Therefore, detailed calculation comparing the HER and NRR should be considered for the design of efficiency NRR catalyst. The comparison of H adsorption and N 2 adsorption was previously employed to determine the selectivity between HER and NRR on metal oxide and nitride surface . Here we also did such kind of comparison as shown in Figure 3C‐E.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, detailed calculation comparing the HER and NRR should be considered for the design of efficiency NRR catalyst. The comparison of H adsorption and N 2 adsorption was previously employed to determine the selectivity between HER and NRR on metal oxide and nitride surface . Here we also did such kind of comparison as shown in Figure 3C‐E.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Zr is an extraordinary exception that has the most positive charge (3.00 |e|) among all the screened Mo 2 TiC 2 O 2 ‐TM SA systems. Positively charged reaction center can significantly polarize and then activate the inert N 2 molecule . Hence, these SACs with considerable positively charged dopant, such as Zr and 5 d transition metals, may greatly facilitate the NRR process.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue that limits NRR in acidic condition is the competition with HER. The protons in solution may occupy the active sites and then form H 2 at a comparable limiting potential, reducing the Faradic efficiency of NRR . As mentioned above, electrostatic repulsion can hinder the binding between proton and the positive charged metal, preventing HER process kinetically.…”
Section: Resultsmentioning
confidence: 99%
“…These binding types exhibit more tunability and are controlled by compositions and crystal structures in comparison to pure metal binding. Through such a tunable binding regulation, not only can the competing HER be suppressed but also an effective electron transfer channel can be established that is conducive for the next activation step.…”
Section: Fundamental Comprehension On Dinitrogen Electroreductionmentioning
confidence: 99%
“…Furthermore, the single atom active components showed intrinsic advantage in suppressing HER. It has been reported that many single atom electrocatalysts have unique electronic structures and lack ensemble effects, both of which hinder H 2 production from hydrogen atoms . For example, Tao et al experimentally showed that single atom Ru anchored at oxygen vacancies suppressed HER ( Figure a) .…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%